2013
DOI: 10.1155/2013/670381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Position on Severity of Obstructive Sleep Apnea: A Systematic Review

Abstract: Aim. The aim of this review is to determine the relationship between sleeping body posture and severity of obstructive sleep apnea. This relationship has been investigated in the past. However, the conclusions derived from some of these studies are conflicting with each other. This paper intends to summarize the reported relationships between sleep posture and various sleep indices in patients diagnosed with sleep apnea. Methods and Materials. A systematic review of the published English literature during a 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 43 publications
6
34
1
1
Order By: Relevance
“…Previous studies investigating body positioning and obesity-associated hypoventilation in patients undergoing NPPV showed that these factors may affect inspiratory and expiratory pressures to achieve a better minute ventilation (MV) [4][5][6]. Patient's comfort and adherence can be improved with the appropriate use of NPPV [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating body positioning and obesity-associated hypoventilation in patients undergoing NPPV showed that these factors may affect inspiratory and expiratory pressures to achieve a better minute ventilation (MV) [4][5][6]. Patient's comfort and adherence can be improved with the appropriate use of NPPV [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…6 Although obstructive events in adults with OSA tend to be worse in the supine position, this finding is less consistent in pediatric literature. 7 Pereira et al 8 found that in children younger than 3 y with OSA, the respiratory disturbance index increased with the increase in time spent in supine sleep but in a later study assessing infants with the age range between 8 to 12 months, the authors found no significant difference between mean supine AHI and non-supine AHI. 8,9 Another study that included children aged 1 to 10 y with OSA suggested that there were less obstructive events in the supine position.…”
Section: Discussionmentioning
confidence: 95%
“…[4][5][6] Also, the effect of position on the distribution of obstructive respiratory events in the pediatric population is not consistent among different studies. [7][8][9][10][11][12] Furthermore, previous studies assessing the effect of sleep stage and position on the distribution of obstructive respiratory events did not explore such effects in a pediatric adolescent population. …”
Section: Introductionmentioning
confidence: 99%
“…However, Menon and Kumar (2013) found a supine sleeping posture is more commonly associated with obstructive sleep apnea (OSA), a common condition in infants, particularly those born prematurely. Katz, Mitchell, and D'Ambrosia (2012) indicate infants have Bboth anatomical and physiological predispositions toward airway obstruction and gas exchange abnormalities including superiorly placed larynx, increased chest wall compliance, ventilation-perfusion mismatching, and ventilatory control instability.^In addition to prematurity, OSA is increasingly common in infants born with Down syndrome (Goffinski et al, 2015), craniofacial conditions, and various other genetic syndromes (Bacher et al, 2011).…”
mentioning
confidence: 99%
“…quality, it has been found that infants and children afflicted with OSA may benefit from sleeping in a lateral position as a systematic review revealed fewer obstructive events in this position (Menon & Kumar, 2013).…”
mentioning
confidence: 99%